Ekspresi Emosi dari Keluarga yang Memiliki Pasien Penyakit Skizofrenia - Saffany Puteri Haniyashfira; Delzi Nurhafifah; Salma Novianti; Vinnatha Syella. Jd; Wirza Feny Rahayu (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Schizophrenia is a syndrome characterized by a disturbance in an individual's behavior that makes the individual's behavior strange. Individuals will also experience delusions, hallucinations and emotions. This study aims to analyze the expression of emotions of families who have family members with schizophrenia. Then also to find out the dynamics and impact on the family. This research is a qualitative research with literature review method by collecting and analyzing relevant articles published from 2014-2024. The form of article collection uses the Google Scholar database. Based on the source of the article, the results obtained show that the emotional expression of the family of schizophrenia patients can affect the frequency of relapse in patients. High emotional expression in patients such as excessive criticism and hostile behavior can cause intense relapse in patients. While low emotional expression and providing more support to patients can reduce the frequency of relapse and improve the recovery process in schizophrenia patients. This study focuses on the importance of emotional management in families and providing more support as an effort to care for schizophrenic patients